Pengaruh Penggunaan Tepung Limbah Udang dalam Ransum terhadap Kualitas Telur Itik - Mirinda Juliambarwati; Adi Ratriyanto; Aqni Hanifa (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2012)
The research aimed to determine the effect of shrimp waste on the quality of duck eggs. The research used 80 female ducks aged 21 weeks which were randomly distributed into four treatments consisted of four replicates of 5 ducks each. The ration consisted of yellow corn, rice bran, soybean meal, fish meal, premix, grit, vegetable oil and shrimp waste. The dietary treatments were formulated to contain 0 (control), 3, 6, and 9% shrimp waste. The experiment was performed for 3 periods of 28 days. Egg quality was assessed for 3 consecutive days on d 26,27 and 28 of every periods. The data were analysed using Analysis of Variance and continued with Duncan’s test for different results. Theuse of 9% shrimp waste in ration increased (P<0.05) score of yolk colour from 6.94 to 7.79, but did not affect other measured variables. It can be concluded that shrimp waste enhanced yolk colour of duck eggs.